Fast‐growing pioneer tree stands as a rapid and effective strategy for bracken elimination in the Neotropics. Issue 5 (28th March 2013) - Douterlungne, David; Thomas, Evert; Levy‐Tacher, Samuel I.
Summary: Large areas of agricultural land around the world are degraded as a consequence of dominance by bracken fern ( Pteridium spp.). Tropical production systems based on shifting cultivation and cattle breeding are particularly vulnerable to invasion of this species. In spite of this, effective methods for tropical bracken control are limited. Fast‐growing tree species have been used successfully to out‐compete aggressively colonizing heliophytes and trigger natural succession. Drawing on a traditional Mayan management technique, we evaluate the potential of the pioneer tree balsa ( Ochroma pyramidale ) to control Pteridium caudatum in Chiapas, Mexico. We tested different bracken cutting frequencies and balsa propagation methods in a factorial randomized block experiment. Eighteen months later, we quantified bracken biomass under the young balsa canopy. Living bracken rhizome biomass correlated significantly with balsa basal area, leaf litter biomass and understorey light intensity. While bracken rhizomes persisted in control plots, it was completely eradicated in plots with a minimum balsa basal area of 11 m 2  ha −1 . This threshold value was reached in less than 18 months with any of the tested propagation methods (seed broadcasting, direct sowing or nursery seedlings), on the condition of at least monthly bracken cutting during the first six months. The ability of fast‐growing broad‐leaved pioneer trees like balsa to quickly out‐compete bracken fern offers opportunities for large‐scale application in tropical rural areas where economic and technical resources are scarce. Synthesis and applications . Mayan subsistence farmers traditionally use balsa to out‐compete invasive weeds, including bracken fern. Here, we highlight the usefulness of this method for quick and effective bracken control in southern Mexico. This approach, in combination with balsa's short rotation cycle, creates opportunities to rapidly convert bracken land into forest stands with commercial potential, thus providing local income and increasing the likelihood of adoption by rural people. We encourage further research to test the potential of balsa and other fast‐growing pioneer trees species for controlling bracken and similar weeds. Abstract : Mayan subsistence farmers traditionally use balsa to out‐compete invasive weeds, including bracken fern. Here, we highlight the usefulness of this method for quick and effective bracken control in southern Mexico. This approach, in combination with balsa's short rotation cycle, creates opportunities to rapidly convert bracken land into forest stands with commercial potential, thus providing local income and increasing the likelihood of adoption by rural people. We encourage further research to test the potential of balsa and other fast‐growing pioneer trees species for controlling bracken and similar weeds.